Mental illness in ancient medicine : from Celsus to Paul of Aegina - Thumiger, Chiara.; Singer, P. N. 1962- (Studies in Ancient Medicine, 2018)
In Mental Illness in Ancient Medicine: From Celsus to Paul of Aegina a detailed account is given, by a range of experts in the field, of the development of different conceptualizations of the mind and its pathology by medical authors from the beginning of the imperial period to the seventh century CE. New analysis is offered, both of the dominant texts of Galen and of such important but neglected figures as Rufus, Archigenes, Athenaeus of Attalia, Aretaeus, Caelius Aurelianus and the Byzantine 'compilers'. The work of these authors is considered both in its medical-historical context and in relation to philosophical and theological debates - on ethics and on the nature of the soul - with which they interacted.